A dose-finding, long-term study on the use of calcium chloride in saline solution as a method of nonsurgical sterilization in dogs: evaluation of the most effective concentration with the lowest risk - Leoci, Raffaella (BioMed Central, 2014)
BACKGROUND: Canine overpopulation is a global issue with serious health and welfare implications. Nonsurgical methods of sterilization could yield positive impacts on this problem, but no long-term data on such methods are available. The objective of the current investigation was to determine the effects of intratesticular injections of calcium chloride dihydrate (CaCl(2)) in saline in dogs over a one year period. Five concentrations (0%, 10%, 20%, 30%, 60%) of CaCl(2) in saline were administered via intratesticular injection to groups of 10 dogs each. Total sperm count and motility, blood levels of testosterone, and side effects were examined at 0, 2, 6, and 12 months post-injection (PI). Testicular size and semen volume were examined at 0 and 12 months PI. RESULTS: Total sperm count, semen volume and testosterone showed significant dose-dependent decreases upon treatment with 10%-60% CaCl(2) compared with either the control group (0% CaCl(2)) or baseline for each treatment group. Azoospermia was achieved for at least 12 months PI in 60% and 80% of treated dogs after administration of a 10% and 20% CaCl(2), respectively. Treatment with 30% or 60% CaCl(2) resulted in azoospermia in 100% of dogs, but more side effects were observed, while no side effects were noticed at lower doses. For each treatment group, testosterone levels had decreased an average of 35%-70% at 6 months following treatment. However, testosterone levels rebounded by the 12-month time point in all groups except the highest dosage group (60% CaCl(2)), which remained at the low end of physiological range throughout the study. Sperm motility dropped to zero or near zero in all dogs treated with CaCl(2). Testicular size was significantly smaller at 12 months PI for all groups when compared to baseline. CONCLUSIONS: This first long-term study confirms reports of the efficacy of CaCl(2) sterilization. However, at dosages free of adverse events, calcium chloride in saline may not provide permanent sterilization as previously believed. Future work should explore optimized solvents to increase the permanence of the well-tolerated 20% formulation.